Environmental, Social, and Governance (ESG) Performance and Corporate Value: Examining the Mediating Role of Operational Efficiency in Indonesian Manufacturing Firms - Nurjannah, Dina; Raharja, Surya (Dinasti Publisher, 2026)
This study examines the effect of Environmental, Social, and Governance (ESG) performance on the value of manufacturing firms listed on the Indonesia Stock Exchange during 2021–2023, with operational efficiency as a mediating variable. Using a quantitative approach with SmartPLS software, ESG performance is measured through Bloomberg’s ESG score, operational efficiency through the Operating Efficiency Ratio, and firm value through Return on Assets. The results show that ESG performance has a positive effect on firm value, while operational efficiency does not significantly mediate this relationship. These findings suggest that the contribution of ESG to firm value is more likely driven by external market perceptions than by internal efficiency improvements, particularly in the short term. This implies that ESG plays a direct role in enhancing firm value, while its indirect effect through operational efficiency remains limited. The study provides practical insights for managers and policymakers on the importance of ESG initiatives in driving firm performance.